One by one - Ware, Ruth (New York : Scout Press, 2020)
When the cofounder of Snoop, a trendy London-based tech startup, organizes a weeklong trip for the team in the French Alps, it starts out as a corporate retreat like any other. But as soon as one shareholder upends the agenda by pushing a lucrative but contentious buyout offer, tensions simmer and loyalties are tested.
Keywords: Employees -- Fiction; Management retreats -- Fiction; Disasters -- Avalanches -- Fiction; Company retreats -- Fiction; Avalanches -- Fiction; Thrillers (Fiction)